Quelques considérations sur le thème du présage de la Passion en Espagne. À propos d'une image "très mystérieuse de la Nativité", tableau retrouvé de Mateo Cerezo (1637-1666) - Lamas-Delgado, Eduardo (RIHA Journal, 2012)
The cult of the Christ Child and his depiction with the Arma Christi expanded enormously during the 17th century, owing to the revival of mysticism spread by the new reformed orders such as the discalced Carmelites and the new Franciscan families. One of the themes developed by this new spirituality was that of the Presage of the Passion, which had spread to some extent during the development of Baroque Classicism in Rome, but whose influence in Spain was more restricted. We will analyse some paintings of this iconographical theme that are linked to Spain or were executed there, and will present for the first time a rediscovered painting by Mateo Cerezo whose unusual iconography was already remarked upon by Palomino.